CHARACTER FORMATION THROUGH AQIDAH AKHLAK MAPEL IN MI AR-RUHAMA, KARDULUK PRAGAAN VILLAGE, SUMENEP - sutini; Ach. Tajib (Akademika : Jurnal Keagamaan dan Pendidikan, 2024)
Character building is a process of understanding the relationships experienced by every human being such as relationships with fellow human beings, God, and the environment. Philosopher Aristotle said that the progress of a nation is determined by 2 things, as: thought and character. This research is affirmed by field research study with a qualitative descriptive type. The methods used are observation methods, interview methods, and documentation methods. Data analysis includes data reduction, data presentation, data analysis. The results of this research showed that the teachers of moral faith at the school had implemented learning using a scientific approach.